Analysis Of Group Islamic Counseling Cognitive Behavior Therapy (CBT) Approach To Improve Students' Self-Esteem At SMPN 6 - Syam, Hidayani (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
When pupils acquire self-confidence, they are able to fully realize their potential, which in turn enhances their academic performance. An examination of the Islamic counseling organization Rational Emotive Behavior's efforts to boost SMPN 6 Padang students' confidence is the primary goal of this research. The researchers in this study used a Nonequivalent Control Group Design experimental strategy. With a total of ten students per group, this design included an experimental treatment group and a control group that did not receive any therapy at all. A self-esteem measure developed by Likert was used to gather data. Based on the findings of this research, pupils whose self-esteem was initially low (negative) were able to improve it to a medium or high level (positive). The results show that students' self-esteem significantly improves when they participate in group counseling sessions that include cognitive behavior therapy.